Analysis and hardware implementation of virtual resistance based PV inverters for harmonics suppression. Issue 20 (10th October 2019) - Zeng, Jiang; Huang, Zhonglong; Ling, Yuchang; Yang, Lin; Li, Zhihua; Qiu, Guobin; Yang, Bo; Yu, Tao
Abstract : Traditional PV inverter is designed for power generation and reducing harmonic distortion without capability of actively participating in harmonic elimination of power grid. This study proposes a virtual resistance based PV inverter to suppress the voltage harmonics at point of common coupling (PCC), in which PV inverters could simultaneously deliver power for fundamental and behave as a series of virtual resistances to absorb power harmonics and then convert them into fundamental power; as a result, voltage distortion of each node of power grid is significantly reduced. No additional sensors are required to measure the non‐linear load current, such that a more flexible installation location of PV inverter can be achieved. Furthermore, current harmonics are controlled by PI controller to track the voltage harmonics multiplied by harmonic conductance, i.e. K h, such that the PV inverter can be equivalent to a virtual resistance. In particular, the absorbed power harmonics are used to evaluate the harmonic suppression, while harmonic conductance K h is regulated automatically to maximise the absorbed power harmonics. Both the simulation and experiment results demonstrate that the effectiveness of the propose method.